Can Information Influence the Social Insurance Participation Decision of China's Rural Migrants? - Giles, John; Meng, Xin; Xue, Sen; Zhao, Guochang (World Bank, Washington, DC, 2018)
This paper uses a randomized information intervention to shed light on whether poor understanding of social insurance, both the process of enrolling and costs and benefits, drives the relatively low rates of participation in urban health insurance and pension programs among China's rural-urban migrants. Among workers without a contract, the information intervention has a strong positive effect on participation in health insurance and, among younger age groups, in pension programs. Migrants are responsive to price: in cities where the premiums are low relative to earnings, information induces health insurance participation, while declines are observed in cities with high relative premiums.